ANALISIS KOMPARATIF STANDAR PROFESI GLOBAL DALAM PENGEMBANGAN ANTARMUKA - Destiarum Gaya Wati; Evy Nurmiati (Jurnal Riset Teknik Komputer, 2026)
The rapid advancement in human-computer interaction demands rigorous professional standardization to ensure the quality and ethics of interface development globally. This study aims to conduct a comparative analysis of global professional standards, with a primary focus on ISO 9241-110 and the rapidly evolving artificial intelligence (AI) interaction guidelines between 2020 and 2025. Using the Systematic Literature Review (SLR) method, this research evaluates relevant literature to identify convergences and divergences between conventional interface design principles and the requirements of modern adaptive interaction. The analysis results indicate that while classical ergonomic principles remain the core foundation, there is a significant shift toward more flexible standards in handling Human-AI interaction. These findings provide insights for information system practitioners and developers in adopting international standards appropriate to the current technological context. In conclusion, the integration between traditional ISO standards and the latest AI guidelines is essential to create interfaces that are not only user-friendly but also professionally accountable.